A validated method of labial minor salivary gland biopsy for the diagnosis of Sjögren's syndrome. (23rd April 2016) - Kim, Jean; Sun, Daniel; Ozl, Rebecca; Grader‐beck, Thomas; Birnbaum, Julius; Akpek, Esen K.; Baer, Alan N.
Abstract : Objectives/Hypothesis: To validate a technique and outcomes of labial minor salivary gland biopsy (LSGB) used for the diagnosis of Sjögren's syndrome (SS). Study Design: Prospective cohort study. Methods: Clinical data were prospectively obtained pre‐ and postbiopsy using patient‐reported questionnaires. LSGB was performed using described methods. Specimens were analyzed by a pathologist with expertise in SS and assessed using established criteria to determine the focus score. Data were analyzed using cross‐tabulations. Results: Among the 58 patients in the study, 52 (90%) presented with sicca symptoms of dry eyes and/or mouth. Eight patients (14%) had histopathologic findings supportive of a diagnosis of SS. At 1 month postbiopsy, greater than 71% of patients denied any complaints of pain, swelling, numbness. or tingling. Sixteen patients (28%) had only a minor level of complaints. Only one patient complained of severe numbness at the biopsy site. Greater than 70% of patients would consider rebiopsy after the procedure, if requested by their physician. Conclusions: We present a safe and effective method of LSGB for the diagnosis of SS. Level of Evidence: 4 Laryngoscope, 126:2041–2046, 2016